Meio ambiente e pobreza entre populações não tradicionais - Marcelo Alario Ennes (Ciências Sociais Unisinos)
This article analyzes the village of Rio das Pedras, which is located around the Serra Ita- baiana National Park in the state of Sergipe. The study was motivated by the need to get to know the population’s socio-environmental reality, which has been recently modified by the creation of a conservation unit. Thus it tries to give visibility to a social group that cannot be called traditional population, but is characterized by its social, economic and political vulnerability. The study was conducted through a combination of techniques to obtain quantitative and qualitative data, which included a literature review and field research. It indicates that, due to their lack of political and theoretical visibility, the non- traditional population groups directly involved in the creation of conservation units are having their living conditions further aggravated and are subjected to a new dynamics of social and political subordination.